Perceived norms and smoking status among secondary school students in Kota Tinggi, Johor, Malaysia - Lim, Kuang Hock; Mohd Ghazali, Sumarni; Kee, Chee Cheong; Abdul Rahman, Hejar; Mustafa, Amal Nasir (Department of Community Health, Universiti Kebangsaan Malaysia Medical Centre, 2012)
Introduction: Social norms, though an important contributing factor of adolescent smoking in developed countries, has not been extensively studied in Malaysia. The objective of this study was to determine the association between certain perceived norms regarding smoking with smoking status among Malaysian secondary school students in Kota Tinggi, Johor. Methods: Data were collected from 2311 respondents consisting of 1379 male and 923 female secondary school students in Kota Tinggi district via a self administered questionnaire. Five perceived norms regarding smoking were assessed, namely: perceived peer smoking prevalence, perceived parental reaction towards adolescent smoking, perceived public perception of adolescent smoking, ever noticed peers smoking inside and outside school and perceived enforcement of anti-smoking policy in school and their association with smoking status. Multiple logistic regressions controlling for gender, peer smoking and family smoking was performed. Results: Of the five perceived norms, four were associated with smoking status, (perceived peer smoking prevalence (p<0.001value), ever seen friends smoking inside or outside school (p <0.001), perceived parental reaction towards adolescent smoking (p<0.001 value) and perceived public disapproval (p <0.001)). Higher odds for smoking was observed for adolescents who: perceived a few (aOR 3.22), many (aOR 3.01) or a lot (aOR 3.52) of their peers smoke; had ever observed friends smoking in or outside of school (aOR 1.79); perceived their parents will react badly to smoking (aOR 0.84) or perceived the public disapprove of smoking (aOR 0.93). Conclusions: These results suggest that perception of social norms influence adolescents’ decision to smoke, thus measures to curb smoking incidence amongst adolescents should address these perceptions of social norms.